Hibernation in an antarctic fish: on ice for winter. - Hamish A Campbell (Public Library of Science (PLoS), 2008)
Active metabolic suppression in anticipation of winter conditions has been demonstrated in species of mammals, birds, reptiles and amphibians, but not fish. This is because the reduction in metabolic rate in fish is directly proportional to the decrease in water temperature and they appear to be incapable of further suppressing their metabolic rate independently of temperature. However, the Antarctic fish (Notothenia coriiceps) is unusual because it undergoes winter metabolic suppression irrespective of water temperature. We assessed the seasonal ecological strategy by monitoring swimming activity, growth, feeding and heart rate (f(H)) in N. coriiceps as they free-ranged within sub-zero waters. The metabolic rate of wild fish was extrapolated from f(H )recordings, from oxygen consumption calibrations established in the laboratory prior to fish release. Throughout the summer months N. coriiceps spent a considerable proportion of its time foraging, resulting in a growth rate (G(w)) of 0.18 +/- 0.2% day(-1). In contrast, during winter much of the time was spent sedentary within a refuge and fish showed a net loss in G(w) (-0.05 +/- 0.05% day(-1)). Whilst inactive during winter, N. coriiceps displayed a very low f(H), reduced sensory and motor capabilities, and standard metabolic rate was one third lower than in summer. In a similar manner to other hibernating species, dormancy was interrupted with periodic arousals. These arousals, which lasted a few hours, occurred every 4-12 days. During arousal activity, f(H) and metabolism increased to summer levels. This endogenous suppression and activation of metabolic processes, independent of body temperature, demonstrates that N. coriiceps were effectively 'putting themselves on ice' during winter months until food resources improved. This study demonstrates that at least some fish species can enter a dormant state similar to hibernation that is not temperature driven and presumably provides seasonal energetic benefits.